(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The dialectics ofviolence, particularly characterizing the partition of the sub-continent,indeed exercised many a creative soul to articulate an artistic response to thelife event. The contours of this creative endeavour, in fact, parallel themultiple manifestations of this phenomenon in actuality that constantly andwith an ever increasing intensity explodes through the fluid and yetuncrystallised socio-cultural and political matrix of India.